2017
DOI: 10.1080/10962247.2017.1301275
|View full text |Cite
|
Sign up to set email alerts
|

The effects of deterioration and technological levels on pollutant emission factors for gasoline light-duty trucks

Abstract: Currently, vehicle emissions are great contributors to air pollution in cities, especially in developing countries. Emission factors play a key role in creating emission inventory and estimating emissions. Deterioration represented by vehicle age and accumulated mileage and changes of emission standards markedly influence emission factors. In addition, the results provide collection factors for implication in the IVE model in the region levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…This is owing to the improvements in both emission control and engine techniques, , as well as the fact that newer vehicles that meet more stringent emission standards typically have driven fewer kilometers. Previous studies have also observed strong correlations between emission and mileage, which is primarily attributed to the deterioration of the three-way catalyst. However, a clear decrease from China 4 to China 5 was not observed though China 4 and China 5 vehicles were in general of lower emissions than China 3 vehicles (Figure S9). On one hand, the actual measured EFs of regulated pollutants from China 4 vehicles (Figure S9) in our study in fact met the emission limits set in the China 5 standard (Table S3).…”
Section: Resultsmentioning
confidence: 79%
“…This is owing to the improvements in both emission control and engine techniques, , as well as the fact that newer vehicles that meet more stringent emission standards typically have driven fewer kilometers. Previous studies have also observed strong correlations between emission and mileage, which is primarily attributed to the deterioration of the three-way catalyst. However, a clear decrease from China 4 to China 5 was not observed though China 4 and China 5 vehicles were in general of lower emissions than China 3 vehicles (Figure S9). On one hand, the actual measured EFs of regulated pollutants from China 4 vehicles (Figure S9) in our study in fact met the emission limits set in the China 5 standard (Table S3).…”
Section: Resultsmentioning
confidence: 79%
“…This is due to an absence of continuous measurement data that reflect the effects of "wear and tear" during the accumulated engine hours. However, based on various studies (Chen and Borken-Kleefeld 2014;Pang et al 2014;Ercan et al 2015;Zhang et al 2017), it has been proven that the rate of exhaust emission increases with hours of engine use. Thirdly, the assumed energy intensity and emission factors, coupled with the assumed engine deterioration model, might have resulted in higher calculated values for the operation phase.…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…Such a simplified deterioration model might prove inadequate for representing real-world processes. For example, Pang et al (2014), Borken-Kleefeld and Chen (2014), Ercan et al 2015, and Zhang et al (2017) showed that engine deterioration and pollutant formation does not propagate linearly. Nevertheless, to the best of our knowledge, there are no alternative distribution models recommended for construction machinery that adequately explain the effect of engine deterioration on the rate of pollutant formation over time.…”
Section: Effective Hourmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have shown that many factors, such as vehicle age and mileage [20], engine technology [21], ambient temperature [22] and inspection and maintenance (I/M) could have a great influence on vehicle exhaust emissions [23]. Heavy duty operation, high mileage and the lack of proper maintenance lead to higher vehicle emissions, resulting in deterioration of the engine and catalyst, and ultimately increased emissions from vehicles in use [24]. To control vehicle exhausts pollution and improve urban air quality, the national government has implemented many control measures, including promoting clean transportation fuel, improving exhaust gas post-treatment technology and formulating strict emission standards.…”
Section: Introductionmentioning
confidence: 99%